FRECUENCIA DE Neospora caninum EN PERROS DE ESTABLOS LECHEROS DEL VALLE DE LIMA - del Campo S., Jorge (2003)
Neosporosis is a parasitic disease caused by Neospora caninum that produces nervous signs in dogs, the definite host, and may affect reproduction in dairy cattle. The objective of the study was to determine the frequency of N. caninum in dogs of dairy farms in the Lima valley. Samples from a total of 104 dogs older than 3 months of age from 23 dairy farms, were collected and analyzed by the indirect immunofluorescense test to detect antibodies against N. caninum. The results indicated that 32.7 ± 9.0% (34/104) were positive to N. caninum in a dilution of 1:50. The Huaura and Huaral provinces had the highest proportion of seropositives (58.8%, 10/17). No significant differences were found due to sex and age.